Epidemiological and clinical characteristics of coronavirus disease 2019 in Daegu, South Korea. (September 2020) - Lee, Ji yeon; Hong, Seung Wan; Hyun, Miri; Park, Jae Seok; Lee, Jae Hyuck; Suh, Young Sung; Kim, Dae Hyun; Han, Seong-Wook; Cho, Chi-Heum; Kim, Hyun ah
Highlights: Among 694 inpatients with COVID-19, 137 patients were classified as severe. No severe case was observed among patients aged ≤ 19 years. Asymptomatic patients accounted for 14.4% of cases. The first outbreak was primarily associated with younger age groups. The number of severe patients and the mortality rate were high in the second outbreak. Abstract: Objectives: Two Coronavirus Disease 2019 (COVID-19) outbreaks simultaneously occurred at a church and a long-term care facility in Daegu, South Korea. This study aimed to investigate the epidemiological characteristics of COVID-19 and factors related to severe outcomes. Methods: We enrolled all inpatients diagnosed with COVID-19 between February 21 and April 2, 2020, in Daegu Dongsan Hospital. We analyzed their clinical and demographic data, laboratory parameters, radiological findings, symptoms, and treatment outcomes. Results: Of 694 patients, severe cases accounted for 19.7% (137 patients). No severe case was observed among patients aged ≤19 years. Hypertension was the most common comorbidity (27%), and cough was the most common symptom (59%). Asymptomatic patients accounted for 14.4% of cases. Lymphopenia, lactate dehydrogenase, C-reactive protein, and albumin were associated with severe outcomes. The first outbreak was mostly associated with younger age groups, and asymptomatic patients mostly showed mild progression. In the second outbreak involving a long-term care facility, both the number of severe patients and the mortality rate were higher. Conclusions: The overall mortality in Daegu was low, which might have resulted from large scale mass screening to detect patients and starting appropriate treatment, including hospitalization for severe cases, and quarantine for asymptomatic patients.